Birds as indicators of HNV: Case study in Portuguese Cork Oak Montados - Rabaça, João E. (2017)
Montados form a heterogeneous landscape of wooded matrix dominated by cork and/or holm oak with open areas characterized by fuzzy boundaries [3]. Montados support high biological diversity associated with low-intensity management and landscape diversity provided by a continuous gradient of land cover [4–7]. Among other features this permits the classification of montados as a High Nature Value (HNV) system. We assessed the role of birds as HNV indicators for montados and tested several bird groups—farmland, edge, forest generalist and forest specialist species; and some universal indicators such as species conservation status, the Shannon diversity index and species richness [8–10]. Our study areas covered the North–South distribution of cork oak in Portugal, and we surveyed breeding bird communities across 117 sampling sites. In addition to variables related to management and sanitary status, we considered variables that characterize the landscape heterogeneity within the montados—trees and shrub density and richness of woody vegetation. Our results suggest that specific bird guilds can be used as HNV indicators of particular typologies of montado, and highlight the need to develop an indicator that could be transversally applied to all types of montado.